2020
DOI: 10.3389/fpsyg.2020.564717
|View full text |Cite
|
Sign up to set email alerts
|

Does COVID-19 Impact Less on Post-stroke Aphasia? This Is Not the Case

Abstract: BackgroundThe coronavirus disease 2019 (COVID-19) pandemic has greatly affected people’s mental health resulting in severe psychological consequences. One of the leading causes of long-term disability worldwide is aphasia. The language changes experienced by a person with aphasia (PWA) often have a sudden and long-lasting negative impact on social interaction, quality of life, and emotional wellbeing. The main aim of this study was to investigate the impact of COVID-19 on the different psychosocial dimensions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…Ahmed et al [25] reported significant increase in post-stroke anxiety and depression related to social deprivation, but the study did not include a comparator group, was limited to small study cohort (n = 52) and included a large proportion of patients of Arab origin. Pisano et al [26] also found increased anxiety in aphasic stroke survivors during the pandemic, but this study cohort was not representative of the full stroke population. By contrast, we included a well-phenotyped and ethnically diverse population of stroke survivors with a control group drawn from the same geographical population.…”
Section: Discussionmentioning
confidence: 84%
“…Ahmed et al [25] reported significant increase in post-stroke anxiety and depression related to social deprivation, but the study did not include a comparator group, was limited to small study cohort (n = 52) and included a large proportion of patients of Arab origin. Pisano et al [26] also found increased anxiety in aphasic stroke survivors during the pandemic, but this study cohort was not representative of the full stroke population. By contrast, we included a well-phenotyped and ethnically diverse population of stroke survivors with a control group drawn from the same geographical population.…”
Section: Discussionmentioning
confidence: 84%
“…One of the very few reports was a recent retrospective interview-based study that investigated how the psychosocial difficulties experienced by Italian PWA have worsened due to COVID-19 (Pisano et al, 2020). A group of 73 chronic PWA previously discharged from rehabilitation services before the COVID-19 emergency were interviewed twice, one month before and one month after the COVID lockdown.…”
Section: Effects Of Covid-19 On Persons With Aphasiamentioning
confidence: 99%
“…Through autonomous networking, the shortage of specialists in the health professions, especially in rural regions (Walter & Altgeld, 2000 Due to the expected positive effects on quality of life and well-being, care of PWA could be optimised. The Covid 19 pandemic has had a major negative impact on the social well-being of all people, especially PWA (Pisano, Giachero, Rugiero, Calati & Marangolo, 2020). The pandemic reinforces the urgency to develop new solutions both for therapy and for PWA, even without therapeutic intervention, to train communication skills (Pisano et al 2020).…”
Section: Data Managementmentioning
confidence: 99%
“…The Covid 19 pandemic has had a major negative impact on the social well-being of all people, especially PWA (Pisano, Giachero, Rugiero, Calati & Marangolo, 2020). The pandemic reinforces the urgency to develop new solutions both for therapy and for PWA, even without therapeutic intervention, to train communication skills (Pisano et al 2020). Digital solutions for communication exchange are therefore also relevant in the future, both to compensate for the negative consequences of the pandemic and to positively enrich the everyday lives of those affected.…”
Section: Data Managementmentioning
confidence: 99%